Analisis de los principales errores de redaccion en las secciones deportes y crónica roja de Diario El Nacional - Intriago Espinoza, Hjalmar Orlando (2016)
The present research is aimed at daily study of the national. In the development of the same will be shown the drafting errors committed by the staff working in the sports and red chronicle sections. To establish what the errors were to be identified, the leonor zozaya article was taken as the guide, which was a great contribution for the development of this work. During a fortnight, from June 13 to June 27, the issues of the journal were collected for later analysis. The contents of each section of the aforementioned sections were tracked. The idea was always to find the factors that lead to the printing of the newspapers in which there is clearly evidence of writing problems. One of the fundamental aspects was not to hold talks or trainings that contribute to the professional knowledge of those who work for the environment, as well as the lack of a manual of styles that serves as a support in the work that communicators do daily. And the aspect that takes more importance is that you have not hired a professional style proofreader who is solely responsible for determining one by one the errors prior to printing so that it can reach the hands of the readers already corrected.